The standardized Withania somnifera Dunal root extract alters basal and morphine-induced opioid receptor gene expression changes in neuroblastoma cells - Francesca Felicia Caputi; Elio Acquas; Sanjay Kasture; Stefania Ruiu; Sanzio Candeletti; Patrizia Romualdi (BMC, 2018)
Abstract Background Behavioral studies demonstrated that the administration of Withania somnifera Dunal roots extract (WSE), prolongs morphine-elicited analgesia and reduces the development of tolerance to the morphine's analgesic effect; however, little is known about the underpinning molecular mechanism(s). In order to shed light on this issue in the present paper we explored whether WSE promotes alterations of μ (MOP) and nociceptin (NOP) opioid receptors gene expression in neuroblastoma SH-SY5Y cells. Methods A range of WSE concentrations was preliminarily tested to evaluate their effects on cell viability. Subsequently, the effects of 5 h exposure to WSE (0.25, 0.50 and 1.00 mg/ml), applied alone and in combination with morphine or naloxone, on MOP and NOP mRNA levels were investigated. Results Data analysis revealed that morphine decreased MOP and NOP receptor gene expression, whereas naloxone elicited their up-regulation. In addition, pre-treatment with naloxone prevented the morphine-elicited gene expression alterations. Interestingly, WSE was able to: a) alter MOP but not NOP gene expression; b) counteract, at its highest concentration, morphine-induced MOP down-regulation, and c) hamper naloxone-induced MOP and NOP up-regulation. Conclusion Present in-vitro data disclose novel evidence about the ability of WSE to influence MOP and NOP opioid receptors gene expression in SH-SY5Y cells. Moreover, our findings suggest that the in-vivo modulation of morphine-mediated analgesia by WSE could be related to the hindering of morphine-elicited opioid receptors down-regulation here observed following WSE pre-treatment at its highest concentration.